FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MEMBAYAR ZIS MENGGUNAKAN GOPAY - Muhammad Fadhil (2022)
The collection of ZIS through GoPay has increased significantly when compared to the collection from previous years, which can be seen from the public interest in donating, especially ZIS, which remains high despite the economic crisis in Indonesia. This study aims to analyze the factors that influence the interest in paying ZIS using electronic money through GoPay. This study uses quantitative research methods with the research population, namely the Jabodetabek people who have paid ZIS through GoPay. The data collection method used primary data in the form of a questionnaire. The sampling technique used purposive sampling technique with the number of respondents as many as 100 people who were taken using the Lemeshow formula. The data obtained were then analyzed using descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. From the results of the study, it was found that there was a significant positive effect between the variables of brand awareness and religiosity partially on interest in paying ZIS using GoPay, but easiness had no effect. Simultaneously, the variables of easiness, brand awareness, and religiosity have a significant influence on the interest in paying ZIS using GoPay.